Children’s Motivation to Learn at Home During the COVID-19 Pandemic: Insights From Indian Parents - Mak, Matthew H. C. (Frontiers in Education, 2021)
The COVID-19 pandemic has forced millions children worldwide to learn at home. Recent reports showed that this had a negative impact on children’s motivation to learn. The current study investigated what factors were associated with a child’s motivation during the pandemic and how parents motivated their children to learn at home. A total of 1,041 parents from India filled out a close-ended survey to help shed light on the issues. The results confirmed that children in India were significantly less motivated to learn during (vs before) the pandemic and revealed that a child’s motivation to learn at home was associated with multiple factors, such as household income, parents’ employment status, child’s academic achievement, and parent’s enjoyment in homeschooling. In contrast, the availability and usage of various technological resources bore no relation to a child’s motivation. Finally, the current data showed that Indian parents most frequently used TV time, words of encouragement, and play/game time as motivators; the least popular motivators were money, new toys, and physical punishment. Exploratory analyses showed that a child’s motivation to learn tended to be lower when parents used more physical punishment to “motivate” their children. These findings were discussed in relation to public/education policies.